Evaluation of the Level of Inclusive Development of the Ukrainian Economy - Zhukovska Alina; Brechko Oleksandr (ECONOMICS)
The problem towards measuring the level of inclusive development of the national economy is one of the most important and controversial problems the modern scientists faced with in the 21st century. The objectives of the named research are the analysis of the various methods of assessing the level of the inclusive development of countries, defining their main advantages and disadvantages, likewise the development of the universal comprehensive method and its use for the further research on the inclusive development of the Ukraine’s economy. The calculation of the integral indicator of the inclusive development of the economy of Ukraine was carried out on the basis of the data of the State Statistics Service of Ukraine according to the author’s methodology using the Excel program. The given method helps to reveal the actual asymmetries in the field of the inclusive development, which should become an analytical basis for making the further managerial decisions. To increase the level of the inclusive development of the economy of Ukraine, it is necessary to: ensure the national security and territorial integrity of the country; improve the institutional support for the inclusive development of the national economy; implement an inclusive approach at all levels of the national economy; stimulate the development of the inclusive entrepreneur-ship; modernize the infrastructure based on the principles of the «universal design»; create conditions for the development of the inclusive education and medicine; stimulate the development of «green», «silver», digital, circular and serial economies.